2017
DOI: 10.1038/s41598-017-12580-4
|View full text |Cite
|
Sign up to set email alerts
|

Ontology-based systematical representation and drug class effect analysis of package insert-reported adverse events associated with cardiovascular drugs used in China

Abstract: With increased usage of cardiovascular drugs (CVDs) for treating cardiovascular diseases, it is important to analyze CVD-associated adverse events (AEs). In this study, we systematically collected package insert-reported AEs associated with CVDs used in China, and developed and analyzed an Ontology of Cardiovascular Drug AEs (OCVDAE). Extending the Ontology of AEs (OAE) and NDF-RT, OCVDAE includes 194 CVDs, CVD ingredients, mechanisms of actions (MoAs), and CVD-associated 736 AEs. An AE-specific drug class eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 86 publications
0
27
0
Order By: Relevance
“…The study design and procedure were similar to the expert user study described below. Participants performed tasks with two different sized ontologies to gauge performance at two distinct levels of difficulty; CVDO [6] (536 classes) and OCVDAE [67] (4,589 classes). Overall, the results showed that Protégé [52] slightly outperformed OntoPlot for most of the Hierarchy-related tasks on both accuracy and completion time.…”
Section: Prototype Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design and procedure were similar to the expert user study described below. Participants performed tasks with two different sized ontologies to gauge performance at two distinct levels of difficulty; CVDO [6] (536 classes) and OCVDAE [67] (4,589 classes). Overall, the results showed that Protégé [52] slightly outperformed OntoPlot for most of the Hierarchy-related tasks on both accuracy and completion time.…”
Section: Prototype Evaluationmentioning
confidence: 99%
“…We use two biomedical ontologies: CVDO [6] and OCVDAE [67]. CVDO (536 classes) was used for the training tasks.…”
Section: Datasetsmentioning
confidence: 99%
“…Once a list of drugs is identified, tools such as Ontofox (Xiang et al, 2010) can be used to extract these drugs and their related characteristics from an ontology and perform specific analyses (Guo et al, 2016;Xie et al, 2016;Wang et al, 2017;Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, an AE-specific drug class effect is defined to exist when all the drugs in a specific drug class (or drug group) are associated with an AE. In a recent study on cardiovascular drug-associated AEs, a proportional class-level ratio (PCR) value was defined and used to identify drug class effect on different AEs [ 15 ]. Specifically, when the PCR value equals to 1, it means that a class effect of a group of drugs on a specific AE exists.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, when the PCR value equals to 1, it means that a class effect of a group of drugs on a specific AE exists. Previous PCR-based heatmap analyses identified many important drug class effects on different AEs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%